STUDI PENGARUH ARAH MEDAN MAGNET DAN CHAMFERED ORIFICE TERHADAP KARAKTERISTIK FLUIDA MAGNETORHEOLOGICAL PADA SAAT TERKENA BEBAN IMPACT - , Intan Paramarti P., M.Agung Bramantya, MT., M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Magnetorheological fluid or usually called as MR fluid is considered as smart fluid due to its ability to change its apparent viscosity if a magnetic field is present. When the fluid is not exposed to any magnetic field, it behaves like Newtonian fluid. However, if there is presence of magnetif fluid near the fluid, the fluid started to behave like non- Newtonian fluid. MR Fluid consists of iron particles which are suspended within carrier fluid such as oil. When magnetic field is present, iron particles within the fluid would be pulled toward the magnetic field direction and each of them would pull other particles. As a result, chains of iron particles are formed within the fluid. The chains of particles make the fluid harder to move and they increase the viscosity of the fluid. MR fluid can be cathegorized as Bingham Fluid by previous researchers. Bingham fluid has yield point which means the fluid wonât flow if the pressure applied to it is below the yield point. In this research, qualitatif analyses of the MR fluid characteristics when subjected to impact load with variation of magnetic field direction were performed. The inclination of orificeâs taper were also varied. The experimental apparatus consisted a U shaped pipe with a piston equipped in one of its side to transmit the impact load. Data measured from these experiments contains the change of pressure of the MR fluid and the change of piston location. Results of the experiments indicates that magnetic field with horizontal direction tend to be weaker than the vertical one. In addition, it is evident that taper 15 was able to damp piston velocity when impact load was applied